The financial literacy of micro business entrepreneurs in Sabah - Salmah Topimin; Siti Rahayu Mohd Hashim (ASIAN SCHOLARS NETWORK, 2020)
The business survival of micro businesses depends largely on a sound financial management. However, the ability of the entrepreneurs of micro business to use financial knowledge and skills in managing their resources effectively is always being debated. This paper addresses this issue by investigating the level of financial literacy of the entrepreneurs of micro businesses in Sabah and its influence on their financial conduct. The data of this study was collected based on in-depth interviews with 15 micro business entrepreneurs. This study found out that the majority of micro business entrepreneurs are not familiar with the basic financial terminology and their views on financial literacy are limited to only certain financial activities such as record keeping and seeking for convenient financial resources, thus indicating the low level of financial literacy. In addition, micro business entrepreneurs in this study are unaware of more complex elements of financial literacy such as the need for financial planning system and the use of a right type of finance structure. The lack of financial literacy among micro business entrepreneurs also has caused them difficulty in accessing external financing. This study is significant as it investigates the issue of financial literacy of micro business entrepreneurs from their own perspectives. Therefore, it provides practical relevance to micro enterprises.